Great Theorists of Central European Integration in France - Pokecz Kovacs, Attila (Great Theorists of Central European Integration, 2023)
France played a key role in the negotiations on the peace treaties that ended the First World War, thus emerging as a major European power and key political player in the Central European region. In the period between the two world wars, French governments in Central Europe sought to preserve the status quo that they had established, and in the course of this process, developed several ideas to integrate the region into Europe. Among the French ideas for the integration of Central Europe, I will first analyse the Briand project. In a 1929 speech, French Prime Minister Aristide Briand proposed a new form of European cooperation. His idea was to create a European Union of 27 European countries, in which the Member States would retain their autonomy, and cooperation would be established primarily in the economic sphere. After a favourable reception, he put his plans into writing, publishing them in 1930. The Briand Plan placed political issues before economic ones, leading to Hungary’s and many other countries’ disappointment. A second idea was the Constructive Plan (‘Plan constructif ’), which was the antonym of the German- Austrian customs union of 1931, drawn up under the leadership of André François-Poncet, Deputy State Secretary, and published in a memorandum on 4 May 1931. In the document, the French government drew attention to four problems: the crisis in the cereals trade in Central and Eastern Europe; situation of the industrialised countries; question of capital and credit; and special situation of Austria. The plan with the most significance was submitted by the French Prime Minister and Minister of Foreign Affairs, André Tardieu, to the British and Italian governments in the form of a memorandum on 2 March 1932. The Tardieu plan was to provide urgent aid to the five Danube states – Austria, Hungary, Czechoslovakia, Romania and Yugoslavia – whose economic situation was close to collapse, mainly as a result of the difficulties caused by the agricultural crisis. However, the fate of the most detailed Central European plan was clearly sealed by the lack of agreement between the great powers, particularly German and Italian opposition, and the position of reluctance adopted by most of the Danube region countries. The Tardieu plan was conceived in February 1932, published in March, and in April it had practically failed. Therefore, none of the three plans developed between 1930 and 1932 was eventually implemented. Following this, no other comprehensive ideas for the integration of the Central European area in 20th Century France have been put forward. KEYWORDS: Tardieu-Plan, Briand-Plan, Central Europe, French Constructif-Plan, Central Europe between the two World Wars